2016
DOI: 10.3233/nre-161371
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation (tDCS) of the primary motor cortex and robot-assisted arm training in chronic incomplete cervical spinal cord injury: A proof of concept sham-randomized clinical study

Abstract: These preliminary findings support that modulating excitatory input of the corticospinal tracts on spinal circuits may be a promising strategy in improving arm and hand functions in persons with incomplete tetraplegia. Further study is needed to explore the underlying mechanisms of recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 31 publications
1
60
0
Order By: Relevance
“…Studies in the area of rehabilitation have indicated that continuous tDCS improved motor function (Costa-Ribeiro et al, 2016; Ilić et al, 2016; Yozbatiran et al, 2016; Figlewski et al, 2017). Thus, continuous tDCS is likely to affect an individual’s AQ score.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the area of rehabilitation have indicated that continuous tDCS improved motor function (Costa-Ribeiro et al, 2016; Ilić et al, 2016; Yozbatiran et al, 2016; Figlewski et al, 2017). Thus, continuous tDCS is likely to affect an individual’s AQ score.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, combination of tDCS and robotic training has shown a promising strategy for improving arm, hand and lower extremity motor functions in persons with incomplete spinal cord injury (Raithatha et al, 2016; Yozbatiran et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…This technique is still in the early stage. To our knowledge, just seven studies have examined improvements in motor function after SCI related to the use of tDCS: four studies evaluated its effect on upper limb function [18][19][20][21] and three studies evaluated the tDCS effect on lower limb function and gait [22][23][24]. All these studies used anodal stimulation and showed improvements in upper and lower limb motor function.…”
Section: Transcranial Direct Current Stimulation (Tdcs)mentioning
confidence: 99%